Beyond a Crime Gene: Genetic Literacy and Correctional Orientation - Graham, Amanda (American journal of criminal justice, 2022)
Is there a "crime gene"? This question has been answered by the scientific community, and the response is a definitive "no." Yet, it is unclear whether this information has been communicated to the general public. Furthermore, it is unclear whether people’s views about the genetics of crime influence their perceptions of the way offenders should be treated. This study uses attribution theory to understand how perceptions of the role of genetic factors in criminal behavior influence beliefs about the punishment, redeemability, and rehabilitation of offenders. Drawing on a national sample of White respondents (N = 392), this study finds that only a small proportion believe there is a single crime gene. Compared to other respondents, those who believe crime is caused by a single gene believe that punishment should be weakened, are less supportive of rehabilitation efforts, and believe that offenders are less capable of redemption. Implications of these findings are discussed.